Crystal structure of trichlorido(4′-ferrocenyl-2, 2′:6′, 2′′-terpyridine-κ3N, N′, N′′)iridium(III) acetonitrile disolvate. (March 2015) - Davaasuren, Bambar; Padhy, Harihara; Rothenberger, Alexander
No abstract available